2022
DOI: 10.3390/life12050756
|View full text |Cite
|
Sign up to set email alerts
|

Human Amniotic Mesenchymal Stem Cells and Fibroblasts Accelerate Wound Repair of Cystic Fibrosis Epithelium

Abstract: Cystic fibrosis (CF) airways are affected by a deranged repair of the damaged epithelium resulting in altered regeneration and differentiation. Previously, we showed that human amniotic mesenchymal stem cells (hAMSCs) corrected base defects of CF airway epithelial cells via connexin (CX)43-intercellular gap junction formation. In this scenario, it is unknown whether hAMSCs, or fibroblasts sharing some common characteristics with MSCs, can operate a faster repair of a damaged airway epithelium. A tip-based scra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 67 publications
(93 reference statements)
0
6
0
Order By: Relevance
“…We have previously shown that CFBE cell monolayers (null for CFTR expression) show a delay in the wound closure. CFBE cells closed the wound only after 48 h, while non-CF 16HBE cells closed the wound in 24 h [ 22 ]. Thus, we investigated the effect of ETI on wound closure.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously shown that CFBE cell monolayers (null for CFTR expression) show a delay in the wound closure. CFBE cells closed the wound only after 48 h, while non-CF 16HBE cells closed the wound in 24 h [ 22 ]. Thus, we investigated the effect of ETI on wound closure.…”
Section: Resultsmentioning
confidence: 99%
“…The defect in wound repair presented by us [ 22 ] and others in various cell models of CF primary and immortalized cell lines [ 19 , 21 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ] strongly suggest that the lack/dysfunction of the CFTR protein may play an essential role. Orkambi ® (lumacaftor/ivacaftor) has been previously shown to significantly increase wound repair rates over a period of 6 h with CF primary airway epithelial cells [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NIH mouse fibroblast cell line (NIH-3T3, a kind gift of Dr. Giuseppe Procino, University of Bari “A. Moro”, Bari, Italy) was grown in Dulbecco’s modified Eagle medium (DMEM) with 4.5 g/L glucose and sodium pyruvate (Corning), containing 10% fetal bovine serum (FBS), 1% L-glutamine, and 1% penicillin/streptomycin [ 64 ].…”
Section: Methodsmentioning
confidence: 99%